Proceedings of the 6th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2017
DOI: 10.7712/120117.5720.18195
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Concrete Frames Strengthened by Tension-Tie Elements Under Cyclic Loading: A Computational Approach

Abstract: Abstract. An efficient numerical simulation of the seismic response of single-story single-span Reinforced Concrete (RC) frames strengthened using diagonal tension-tie elements is presented. The developed analysis is based, calibrated and verified on test results of bare and X-braced RC frames subjected to cyclic imposed lateral deformations described in a companion paper. The dimensional and the reinforcement configurations of the frames represent earlier RC frame structures that have been designed using old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The herein obtained experimental results are used in a companion paper [24] for the calibration of a numerical approach concerning the hysteretic response of RC frame structures strengthened by tension-tie elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The herein obtained experimental results are used in a companion paper [24] for the calibration of a numerical approach concerning the hysteretic response of RC frame structures strengthened by tension-tie elements.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that through the use of steel braces enhances the seismic performance of the strengthened frame improving strength, stiffness and energy dissipation capacity. A specific category in the brace strengthening technique of existing RC frames concerns the use of X-type cable elements [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…After the seismic assessment [1][2][3][4][5][6]12] of RC frame F0, the need for seismic upgrading has been resulted. Thus, the X-cable bracing system F6, as shown in Figure 3, has been proposed in order the frame F0 to be seismically strengthened.…”
Section: Numerical Examplementioning
confidence: 99%
“…The sequence of events E 1 and E 2 is denoted as Event (E 1 + E 2 ). In column [3] the mean value and in column [4] the coefficient of variation (COV) of the Global Damage Indices (DI G ) are given. Similarly, in columns [5] and [6], the mean value and COV of the absolutely maximum horizontal top roof displacement (u top ) are given.…”
Section: Numerical Examplementioning
confidence: 99%
See 1 more Smart Citation